Study and design of a cutting mechanism - Zachariah, Jacob (2011)
In this modern world where the chemical and pharmaceutical industries dealt with different kinds of chemicals and samples, various types of testing or experiments are conducted to achieve the results related to different branches. So those kinds of experiments or testing’s are inevitable and the frequency will increase further in the future. However, during the testing of those chemicals there are chances for accidents or contamination which will be harmful to the human health. Accidents or contamination can be occurred due to several reasons like chemical spillage, damaged chemical bottle during the process etc. Damage to the chemical bottle can be occurred during the unsealing process which will be done before conducting the experiment. There will be several reasons which can lead to the damage of the chemical bottle. Reasons like negligence, human error, poor training etc can cause the damage to the bottle during the unsealing process. To prevent this problem and also to improve the efficiency of the unsealing process, a bottle unsealing device is required.